Norway : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1999)
This Selected Issues paper reviews the main elements of the National Insurance Scheme (NIS) and the Family Allowance Scheme (FAS) in Norway and provides projections of future pension expenditures. All persons residing or working in Norway are insured under the NIS, and the system is financed on a pay-as-you-go basis through contributions and from general tax revenue. The paper demonstrates that indexing pensions to wages, in line with recent practice, would result in a large net liability by the year 2050, which could be reduced by indexing pensions instead to consumer prices.